Donald Ross pioneer evangelist of the north of Scotland and United States of America - Ross, Charles W. (Kilmarnock, Scotland John Ritchie)
Includes selections by Charles W. Ross, Donald Munro (1839-1908, Toronto), John Ritchie (1853-1930 Kilmarnock), George Adam (1830?-1907 Kennethmont), Caleb Jason Baker (d. 1918), Thomas D.T. Muir (1855-1931 Detroit), et al.
Publisher's blurb inside front cover suggests published in 1903.
Keywords: Ross, Donald, -- 1824--1903 -- Brethren movement -- evangelist -- biography